2009
DOI: 10.1107/s1600536809037313
|View full text |Cite
|
Sign up to set email alerts
|

Guanidinium 3-carboxy-2,3-dihydroxypropanoate monohydrate

Abstract: In the title hydrated salt, CH6N3 +·C4H5O6 −·H2O, the deprotonated carboxyl group is disordered over two positions with a site-occupancy ratio of 0.945 (3):0.055 (3). The bond lengths in the guanidinium cation are inter­mediate between normal C—N and C=N bond lengths, indicating significant delocalization in this species. In the crystal structure, anions and water mol­ecules are linked into sheets parallel to the ab plane by inter­molecular O—H⋯O hydrogen bonds. The linking of the anions and water mol­ecules w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…Comparing with the unprotonated structure (De cires- Mejias et al, 2004), protonation of atoms N1 & N4 have widened the C-N-C angles to 123.51 (8) and 123.92 (9)°, respectively, for angles of C5-N1-C9 and C10-N4-C14. The bond lengths (Allen et al, 1987) and angles observed are within normal ranges and are consistent with those related structures (Al-Dajani, Abdallah et al, 2009;Al-Dajani, Salhin et al, 2009).…”
Section: Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…Comparing with the unprotonated structure (De cires- Mejias et al, 2004), protonation of atoms N1 & N4 have widened the C-N-C angles to 123.51 (8) and 123.92 (9)°, respectively, for angles of C5-N1-C9 and C10-N4-C14. The bond lengths (Allen et al, 1987) and angles observed are within normal ranges and are consistent with those related structures (Al-Dajani, Abdallah et al, 2009;Al-Dajani, Salhin et al, 2009).…”
Section: Methodssupporting
confidence: 87%
“…For related structures, see: Al-Dajani, Abdallah et al (2009); Al-Dajani, Salhin et al (2009). For hydrogen-bond motifs, see: Bernstein et al (1995).…”
Section: Related Literaturementioning
confidence: 99%
“…The C1-N1 and C1-N2 bond lengths in the propeller-shaped guanidinium cation are almost equal [1.3310 (14) and 1.3289 (8) Å respectively], indicating that the usual model of electron dislocalization in this moiety (Allen et al, 1987). The bond lengths and angles are comparable to closely related guanidinium (Al-Dajani et al, 2009) and chlorochromate (Lorenzo Luis et al, 1996) structures.…”
Section: Methodsmentioning
confidence: 61%
“…For graph-set descriptions of hydrogen-bond motifs, see: Bernstein et al (1995). For related structures, see: Al-Dajani et al (2009); Lorenzo Luis et al (1996). For the stability of the temperature controller used for the data collection, see: Cosier & Glazer (1986).…”
Section: Related Literaturementioning
confidence: 99%
“…For general background to citric acid and guanidine, see: Raczyń ska et al (2003); Yamada et al (2009); Sigman et al (1993). For a related structure with a guanidinium cation, see: Al-Dajani et al (2009). For hydrogen-bond motifs, see: Bernstein et al (1995).…”
Section: Related Literaturementioning
confidence: 99%